The application of passive air jet vortex-generators to stall suppression on wind turbine blades - Prince, Simon A.; Badalamenti, Carmine; Regas, Constantinos (Wiley, 2016)
An experimental study was performed to assess the feasibility of passive air jet vortex-generators to the performance enhancement of a domestic scale wind turbine. It has been demonstrated that these simple devices, properly designed and implemented, can provide worthwhile performance benefits for domestic wind turbines of the type investigated in this study. In particular, this study shows that they can increase the maximum output power coefficient, reduce the cut-in wind speed and improve power output at lower wind speeds while reducing the sensitivity to wind speed unsteadiness. A theoretical performance analysis of a 500 kW stall-regulated wind turbine, based on blade element momentum theory, indicates that passive air jet vortex-generators would be capable of recovering some of the power loss because of blade stall, thereby allowing attainment of rated power output at slightly lower average wind speeds
Keywords: passive flow control; vortex-generators; aerodynamics; stall suppression